Species Distribution Modeling of Endemic Jurinea (Asteraceae) Species Shows Opportunistic Results for Their Conservation - Sirojiddina, Toshmirov; Muzaffar, Djuraqulov; Akram, Ibragimov (American Journal of Biology and Natural Sciences, 2026)
Climate change is expected to alter the distribution patterns of endemic mountain flora, yet species-specific responses remain poorly understood in Central Asia. We modeled the current and future potential distributions of five endemic taxa under SSP1–2.6 and SSP5–8.5 climate scenarios for 2050 and 2070. The results revealed pronounced interspecific differences in climatic sensitivity. Three species (J. asperifolia, J. sangardensis, and J. zakirovii) showed substantial expansion of climatically suitable areas under both scenarios, with projected increases ranging from 90% to 180% relative to present conditions. In addition to the Pamir-Alay region, the western Tien Shan emerged as a potentially suitable area, suggesting additional climatic refugia. In contrast, J. gracilis exhibited severe habitat contraction across all projections, including complete loss of suitable area under SSP5–8.5 by 2070, indicating high extinction risk. J. mariae demonstrated moderate expansion and relative stability. These contrasting patterns highlight strong interspecific variation in climatic tolerance within a single genus. However, projected expansion does not necessarily guarantee realized range shifts, as dispersal limitation and habitat fragmentation may constrain colonization. Overall, the findings emphasize the need for species-specific conservation strategies to mitigate climate-driven biodiversity loss in endemic mountain ecosystems.